Acceleration analysis of population growth using winter's method: case study of lombok island. (October 2020) - Negara, H R P; Syaharuddin; Ibrahim, M; Kurniawati, K R A; Mandailina, V; Pramita, D; Abdillah; Mahsup; Ahmad; Saddam
Abstract: The research aims to analyze the acceleration of the population growth in Lombok which consists of 5 districts/cities using forecasting system by constructing the winter's method in the form of a GUI Multiple Forecasting System (G-MFS) based on Matlab by calculating the indicator level of accuracy to find predictive data for the next 10 years. At the data simulation stage, researchers used population data over the last 11 years. The evaluation of forecasting results is calculated by calculating the value of Mean Absolute Percentage Error (MAPE) with 27 attempts through modified Winter parameter values. From the simulation data obtained the most optimal parameter value is α, β, and γ sequential values of 0.9, 0.5, and 0.9. Then with the value of the parameter obtained MAPE value of 1.25%. Furthermore, it can be noted that for the next 10 years the increase in the population of Lombok Island on average of 1.49%, with the average East Lombok district details of 1.15%, the average West Lombok district by 1.17%, the average central Lombok district of 0.98%, the North Lombok district averaged 0.98%, and the average Mataram city of 3.05%. These results suggest that the simulated and numeric techniques using the GUI of MATLAB provide quite accurate results. In subsequent research, it is necessary to do predictions based on the number of births, the number of deaths, the number of transmigration, the amount of productive and non-productive, and other data series that is more complex so that it will be seen how the development of the population productivity on the island of Lombok.